Integrated Curriculum Management with Local Content in Improving the Quality of Institutions at MA Raudlatul Ulum Putri - Tazkiyah, Ianatut; Abidin, Munirul; Malik Karim Amrullah, Abdul (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
The competence of students is developed by educational institutions in an effort to achieve educational visions and missions based on educational goals. Policies related to student graduation at this time are not based on the results of the National Examination, but are based on school/madrasah decisions. Madrasas have a responsibility for the graduation predicate of students. Graduation criteria are determined by each educational unit. Thus, the value of local content is also considered in graduation. Not only implementing educational goals in general, but the values of local wisdom must also be in the curriculum. The objectives of the study were to find out, (1) the integrated curriculum planning model used in developing student competencies at MA Raudlatul Ulum Putri, (2) how to organize an integrated curriculum with local content, (3) how to implement an integrated curriculum with content, (4) how curriculum evaluation is integrated with local content. This type of research is descriptive qualitative with a case study approach. The research began in November 2021-January 2022 at the MA Raudlatul Ulum Putri Ganjaran Gondanglegi Malang. Collecting data through observation, interviews and documentation. Meanwhile, the data analysis techniques are data reduction, data presentation and verification. Checking the validity of the data used triangulation of sources, methods and data. The results of this study are (1) the planning used in developing an integrated curriculum using the rational-interactive model, (2) the organization used is curriculum integration, globally it is integrating the curriculum of the Ministry of Religion and Local Content (kitab turats). In particular, integrated interdisciplinary science. (3) The implementation of the curriculum is guided by the Decree of the Minister of Religion Number 184 of 2019, but replaces some group B subjects with other local content. (4) Curriculum evaluation is that the lesson plans have not been fully realized. The minority of students are not alumni of Islamic boarding schools or madrasas, so they are not familiar with the turats book when they first enter the madrasa and need to maximize the Book Reading Guidance (BMK) specifically for new students who are still lacking in their ability to learn the turats book.